Modernist Women's Writing: Beyond the Threshold of Obsolescence. Issue 1 (24th January 2013) - Garrity, Jane
Abstract The new modernist studies has helped to expand the definition of modernism, but this move has simultaneously contributed to the marginalization of "women's writing." The rise of post‐structuralism, transnational and race studies, as well as queer and transgender theory, have all contributed to a more complicated and nuanced understanding of gender‐based analyses and their political import. However this move to expand the range and scope of our understanding of gender raises inevitable questions about the viability of the category of "modernist women's writing." This essay asks: What is the rationale for retaining a focus on "women's writing"– and, more particularly, on experimental women's writing – within modernist studies today, and how can we signal the continued vitality of this gender‐inflected area of scholarship without succumbing to the bewildering label, old‐fashioned?